2020
DOI: 10.1109/jtehm.2020.2999725
|View full text |Cite
|
Sign up to set email alerts
|

DFENet: Deep Feature Enhancement Network for Accurate Calculation of Instantaneous Wave-Free Ratio

Abstract: Accurate iFR calculation can provide important clinical information for intracoronary functional assessment without administration of adenosine, which needs to locate object points in the pressure waveforms: peak, the dichrotic notch and the pressure nadir at the end of diastole. We propose a DFENet that is capable of locating object points to calculate iFR accurately. We first design a SFRA into DFENet with the idea of DenseNet. To avoid overfitting when dealing with sparse signals, we set appropriate number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…We believe that this may be caused by over-tting of DenseNet. Previous studies have shown that over tting of the model leads to a decrease in accuracy 35,36 . Because DenseNet has more connections than ResNet, its performance may be improved by debugging some parameters 25,37 .…”
Section: Resultsmentioning
confidence: 99%
“…We believe that this may be caused by over-tting of DenseNet. Previous studies have shown that over tting of the model leads to a decrease in accuracy 35,36 . Because DenseNet has more connections than ResNet, its performance may be improved by debugging some parameters 25,37 .…”
Section: Resultsmentioning
confidence: 99%